ANALYSIS OF SOME AUXILIARIES IN THE OʻGʻUZ DIALECT OF THE UZBEK LANGUAGE (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article discusses the Oguz dialect of the Uzbek language, some of its specific linguistic features, as well as the use and role of auxiliaries in this dialect. It is explained with examples taken from dialectological materials related to the Oguz dialect.